Problem Based Learning Model Integrated with Islamic Values on Global Warming Material - Yusriani, Yusriani (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This article is driven by the necessity for a learning approach that enhances students' cognitive capacities while simultaneously cultivating spiritual character and understanding of increasingly intricate global environmental challenges. The research employs a descriptive qualitative methodology utilizing a literature review approach. Data were acquired from pertinent national and international journal articles published from 2015 to 2025. The findings indicate that the application of the problem-based learning model in physics education enhances students' cognitive dimensions while also cultivating scientific attitudes and 21st-century competencies, including conceptual comprehension, problem-solving skills, critical and creative thinking, and scientific process skills. The subject of global warming is intrinsically linked to fundamental concepts of physics and enhances students' ecological consciousness, particularly in addressing global challenges like the climate catastrophe. Moreover, the incorporation of Islamic principles in physics instruction regarding global warming adds a spiritual dimension that enhances the scientific learning experience. Values such as integrity, leadership, moderation, and ethical stewardship of nature render education not solely the conveyance of knowledge but also the cultivation of a comprehensive character. Islamic doctrines promoting environmental conservation can foster a collective consciousness on the significance of safeguarding the land as a trust from God. The integration of problem-based learning (PBL) with Islamic ideals in the study of global warming is a comprehensive and transformative methodology that enhances students' academic proficiency while simultaneously cultivating their spiritual, social, and ecological character.